Investigating the Effect of Ultrasonic and Microwave-Assisted Aging on the Synthesis of Nanosized SAPO-34 Molecular Sieves Using Box–Behnken Experimental Design. Issue 5 (3rd May 2016) - Pajaie, Hassan Sharifi; Taghizadeh, Majid
Abstract : Nanosized SAPO-34 was synthesized by means of ultrasonic and microwave-assisted aging process. Synthesized samples were characterized by BET, XRD, and FE-SEM techniques. Applying the response surface methodology (RSM) based on Box–Behnken statistical design, the effects of microwave (MW), ultrasonic (US) aging time, and hydrothermal time on the preparation of SAPO-34 with respect to crystallinity of final product phase were investigated. The results showed that the interaction between US and MW aging time had the main positive effect on the crystallinity and the crystallization was accomplished in a significantly reduced time.